2013
DOI: 10.1371/journal.pone.0061992
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer KIR3DS1 Is Closely Associated with HCV Viral Clearance and Sustained Virological Response in HIV/HCV Patients

Abstract: AimTo evaluate the influence of the presence of the killer cell immunoglobulin-like receptor (KIR) 3DS1 on HCV treatment response in HIV/HCV genotype 1 co-infected patientsMethodsHIV/HCV co-infected patients were included. KIR3DS1, their specific HLA-B ligands and IL28B gene were genotyped. Reductions of plasma HCV RNA levels between baseline and week 1, week 2 and week 4 were analyzed for IL28B genotype and KIR3DS1 (HLA Bw4 or Bw6). Rapid and sustained virological response (RVR and SVR) rates were also analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…As regard to the function of cells (perforin production) by both NK and NKT cells, it was significantly decreased (P value was 0.012 and 0.001, respectively). Meier et al, (2005) and Rivero et al, (2013) detected similar results to that of our study, They revealed that this shift influenced phenotype and functional capacity (gamma interferon production capacity of the NK subset CD 56dim observed in HIV and HCV patient were found to be associated with a significant reduction in serum levels of the innate cytokine interleukin 15 (IL-15). CD 56 dim and CD 56bright subsets differ in their perforin content, where CD 56bright cells are low in perforin, CD 56dim cells express higher levels of perforin.…”
Section: Resultssupporting
confidence: 88%
“…As regard to the function of cells (perforin production) by both NK and NKT cells, it was significantly decreased (P value was 0.012 and 0.001, respectively). Meier et al, (2005) and Rivero et al, (2013) detected similar results to that of our study, They revealed that this shift influenced phenotype and functional capacity (gamma interferon production capacity of the NK subset CD 56dim observed in HIV and HCV patient were found to be associated with a significant reduction in serum levels of the innate cytokine interleukin 15 (IL-15). CD 56 dim and CD 56bright subsets differ in their perforin content, where CD 56bright cells are low in perforin, CD 56dim cells express higher levels of perforin.…”
Section: Resultssupporting
confidence: 88%
“…Kusnierczyk et al reported that KIR2DS2 may contribute to the susceptibility to CHC in Polish Caucasians (Kusnierczyk et al, ), while Sung, et al suggested it might be associated with HCV clearance in the Korean population (Sung et al, ). Rivero‐Juarez et al found that KIR3DS1 genotype has a positive effect on HCV viral clearance during the first weeks of Peg‐IFN/RBV treatment in HCV/HCV co‐infected patients bearing genotype 1 (Rivero‐Juarez et al, ). In the present study, we observed no association of CHC and KIR2DS3 .…”
Section: Discussionmentioning
confidence: 99%
“…KIR genotype has been recently reported to be a significant factor in the control of primary cytomegalovirus infection16 and an interesting study also showed that KIR3DS1 is closely associated with hepatitis C virus (HCV) clearance and sustained virological response in HIV/HCV patients 17…”
Section: Discussionmentioning
confidence: 99%